Microorganisms associated with Sporobolus anglicus, an invasive dimethylsulfoniopropionate producing salt marsh plant, are an unrecognized sink for dimethylsulfide - Kröber, Eileen; Mankowski, Anna; Schäfer, Hendrik (Frontiers in Microbiology, 2022)
Background: Saltmarshes are hotspots of organosulfur compound cycling due to production of dimethylsulfoniopropionate (DMSP) by benthic microorganisms, macroalgae and saltmarsh vegetation. Degradation of DMSP is a source of dimethylsulfide (DMS), an important precursor for formation of secondary organic aerosol. Microorganisms degrading DMS play a role in controlling the amount of DMS available for emission into the atmosphere. Previous work has implicated sediment microbial populations as a major sink for DMS. Here we show that Sporobolus anglicus (previously known as Spartina anglica), a widely distributed saltmarsh plant, is colonized by DMS-degrading microorganisms. Methods: DMS degradation potential was assessed by gas chromatography and 13C-DMS stable isotope probing, microbial community diversity and functional genetic potential in phyllosphere and rhizosphere samples was assessed by high-throughput sequencing of 16S rRNA gene amplicons, cloning and sequencing of methanethiol oxidase genes, and by metagenomic analysis of phyllosphere microbial communities. Results: The DMS degradation potential of microbial communities recovered from phyllosphere and rhizosphere samples was similar. Active DMS-degraders were identified by 13C-DMS stable isotope probing and included populations related to Methylophaga and other Piscirickettsiaceae in rhizosphere samples. DMS-degraders in the phyllosphere included Xanthomonadaceae and Halothiobacillaceae. The diversity in sediment samples of the methanethiol oxidase (mtoX) gene, a marker for metabolism of methanethiol during DMS and DMSP degradation, was similar to previously detected saltmarsh mtoX, including those of Methylophaga and Methylococcaeae. Phyllosphere mtoX genes were distinct from sediment mtoX and did not include close relatives of cultivated bacteria. Microbial diversity in the phyllosphere of S. anglicus was distinct compared to those of model plants such as rice, soybean, clover and Arabidopsis and showed a dominance of Gammaproteobacteria rather than Alphaproteobacteria. Conclusion: The potential for microbial DMS degradation in the phyllosphere and rhizosphere of Sporobolus anglicus suggest that DMS cycling in saltmarshes is more complex than previously recognised and calls for a more detailed assessment of how aboveground activities affect fluxes of DMS.